Thirty-Day Readmission Predicts 1-Year Mortality in Acute Pancreatitis. Issue 4 (April 2016) - Lee, Peter J.W.; Bhatt, Amit; Lopez, Rocio; Stevens, Tyler
Abstract : Objectives: There is limited knowledge of the prognostic indicators after hospital discharge after acute pancreatitis (AP). The aim was to determine risk factors for mortality after discharge in patients admitted with AP. Methods: A retrospective cohort study was conducted, including consecutive patients with AP admitted to the Cleveland Clinic between 2007 and 2011. Clinical data, mortality status, and the date of death were collected. Univariable and multivariable Cox regression was performed to determine variables significantly associated with mortality within a year of discharge. Results: Three hundred thirty-one patients were included in the study, current to July 2012. After a mean follow-up of 20 months, 41 subjects (12.4%) died after discharge from the hospital. Thirty-three (10.0%) died within a year after discharge. In univariable analyses, higher Charlson Comorbidity Index, blood urea nitrogen > 20 on admission, higher Bedside Index of Severity in Acute Pancreatitis scores, longer length of stay, and readmission within 30 days were associated with a higher hazard of mortality. In the multivariable analysis, subjects who were readmitted within 30 days had a 4.5 times higher hazard of dying within a year than those who were not readmitted (hazard ratio, 4.5; 95% confidence interval, 2.2–9.1). Conclusion: A higher Charlson Comorbidity Index, early readmission, and longer hospitalization predict a higher 1-year mortality after AP.